MANAJEMEN IDENTITAS DAN AKSES DALAM KEAMANAN SISTEM INFORMASI (PENDEKATAN LITERATURE REVIEW) - Gemawaty, Cut Asiana; Yuliani, Yuce (Jurnal Manajamen Informatika Jayakarta, 2024)
Identity and Access Management (IAM) is a crucial element in ensuring the security of information systems within an organization. This study aims to explore the concepts, techniques, and implementations of IAM in the context of information system security through a literature review approach. With identity federation systems and Single Sign-On (SSO), organizations can improve efficiency in managing user identities and access to various applications or services without the need for repeated login processes. Identity federation allows users to access services from different organizations using the same credentials, reducing administrative burdens and enhancing user experience. SSO, as a core component of IAM, enables users to access multiple applications with a single login, simplifying access management and increasing productivity. However, security challenges remain, especially concerning data leakage risks and potential attacks exploiting its vulnerabilities. Implementing security technologies such as multi-factor authentication and role-based access management can mitigate such threats. This study concludes that effective IAM is essential for the continuity and security of information systems in modern organizations.